The Sword with the Sleeve Cross-Guard in the Fresco from the Cathedral of the Holy Cross on Aghtamar Island - D’Amato, Raffaele; Dymydyuk, Dmytro (Studia Ceranea, 2021)
There is an indisputable fact that in Medieval Armenia, as in most countries of the Middle Ages, the sword was a popular (but expensive) type of weapon. However, what did these “swords” look like? The aim of the article is to analyse one internal fresco called “Massacre of the Innocents” from Aghtamar Church (915–921), where a depiction of the sword with the sleeve cross-guard could be found. Comparisons of the known archaeological finds of “Byzantine” type swords from Eastern Europe and Near East have been made, proving the idea that such type of swords actually existed. The authors, with the following analysis, would like to support the idea that medieval figurative sources are a very accurate for studying medieval military history.